2017
DOI: 10.1007/s10792-017-0489-3
|View full text |Cite
|
Sign up to set email alerts
|

Heavy and standard silicone oil: intraocular inflammation

Abstract: Both regular and heavy silicone oils usually yield good success rates in cases of complicated retinal detachment. Decisions as to whether to utilize heavy or regular silicone oil should be made on a case-by-case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 56 publications
0
38
2
4
Order By: Relevance
“…Study showed, growth factors, such as basic fibroblast Growth Factor (bFGF) in PVR patient is also higher when compared with patients with macular holes or idiopathic premacular fibrosis [14]. Some studies suggest that the macrophage will release enzyme on PVR resulting in vitreous structure changes as a result of the protein matrix proteolysis and also the formation of fibrotic membranes to synthesis the fibroblast growth factor by macrophages [15].…”
Section: Discussionmentioning
confidence: 99%
“…Study showed, growth factors, such as basic fibroblast Growth Factor (bFGF) in PVR patient is also higher when compared with patients with macular holes or idiopathic premacular fibrosis [14]. Some studies suggest that the macrophage will release enzyme on PVR resulting in vitreous structure changes as a result of the protein matrix proteolysis and also the formation of fibrotic membranes to synthesis the fibroblast growth factor by macrophages [15].…”
Section: Discussionmentioning
confidence: 99%
“…11,12,13,14,15,16,17 A recent meta-analysis has shown that the complication spectrum of these new-generation HDSOs seems to be similar to that of conventional silicone oil tamponades. 18 These two approved heavier-than-water silicone oil tamponades, Oxane Âź HD and Densiron Âź 68, are commonly used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of endotamponades have certain defects in various surgical procedures, such as existing gas and liquid tamponades, which can not provide good support for the lower retina, resulting in a higher failure rate of retinal detachment under the lower hole. Therefore, in order to improve the healing of the underlying retinal tears, there are two heavy silicone oil products approved as intraocular tamponades for clinical use in Europe, Oxane HD (siliconefluorinated paraffin mixture) and Densiron (silicone-heavy water mixture) [2] . Heavy silicone oil solves the problem of the lower retinal detachment in some extent and help for the retina reattachment, whereas many of its complications have also been observed in clinical applications, such as cataract, intraocular light-to-moderate inflammatory response and increased intraocular pressure, etc [3] .Therefore, vitreous tamponades with good biocompatibility, stable properties, and no recipient limitation, should be developed to effectively press the retinal tears with different orientations [4] .…”
Section: Introductionmentioning
confidence: 99%